Alexander Neckam: Chess in De naturis rerum (Circe de clásicos y modernos, 2023)
This paper offers, to the best of our knowledge, the only translation into spanish of the chapter “On Chess” of the encyclopedic work De naturis rerum written around 1190 by the english philosopher Alexander Neckam (1157-1217). The mentioned chapter, which follows another one on dice players, is relevant not only to understand the continuity of an anti-ludic attitude that has its roots in the thought of the first Christians, but also to notice the reception of muslim chess in christian medieval England both in its symbolic representations and in the rules of the game.
Keywords: Neckam; De naturis rerum; Christianity; games; chess